#TITLE_ALTERNATIVE# - PIAN NOPIANA (NIM 12304015); Pembimbing: DR. Eng. Ir T. A. Sanny, MSc., AA
Seismic reflection of zero stack offset profile is the first profile that can be interpreted before the next processing step, so that the quality of zero offset stack profile has a very significant role.In addition, a fine zero stack offside profile is really needed as an input of migration process so that the profile of the migration result will give a better quality.One of the stack methods that can give a better result is Common Reflection Surface (CRS) stack.This Method uses some ideas and principals from convensional CMP stacking.The basic difference is in the number of trace used in CRS which is more in quantity than ones used in CMP stack. In this research, CRS stack was examined in complex structuress of geologic conditions, like unconformity and steep dip,in this research I choosed marmousi model.CRS stack gives a correction in stack quality remarked by the reflector continuosity, signal to noise ratio improvement, and also gives an image correction after post-stack migration.